An Analysis of Indonesian Young Learner's Reading Ability in Remote Area - Satria Pugar Alam (International Journal of Educational Technology Research, 2023)
This research aims to identify the reading ability of Indonesian young learners in remote area. This research applied descriptive quantitative method by using EGRA (Early Grade Reading Assessment) test instrument. The researcher used first-grade students at SDN Ngolo as sample. The researcher measured all the students from first-grade students at SDN Ngolo which consist of 14 students. The result of this research showed that the reading ability of 1st grade students in SDN Ngolo is on very poor category with the score 53,6. From 14 students of 1st grade who followed the test, 1 student is categorized as very good, 3 students are categorized as good, 4 students are categorized as fair, 0 student is categorized as poor, and 6 students are categorized as very poor. The most dominant reading ability of 1st grade students in SDN Ngolo is the ability to recognize the letter with 70,2857 (fair) score. The lowest reading ability of 1st grade students in SDN Ngolo is the ability to read fluently and the ability to comprehend the text with 28,5714 (very poor) score.